Analysis Of The Role Of Local Governments In Sustainable Development In Urban Areas - Syafaruddin Syafaruddin (Digital Innovation : International Journal of Management, 2024)
This study aims to analyze the role of local governments in the implementation of sustainable development policies in urban areas. Using a qualitative approach through case study methods, data were collected via in-depth interviews with local government officials, focus group discussions with community members, and analysis of policy documents and local development reports. The findings indicate that local governments play a vital role in creating positive impacts on the environment and the quality of life for residents through various implemented programs, such as integrated waste management systems, the development of green open spaces, and sustainable transportation policies. Despite significant progress, this research also identifies challenges faced by local governments, including funding limitations, a lack of community education, and the need for improved inter-agency coordination. To enhance their effectiveness in achieving sustainable development goals, local governments must address these challenges through increased budget allocations, educational campaigns to raise community awareness, and strengthened collaboration among agencies. By taking these steps, local governments can be more effective in realizing sustainable development and ensuring a better quality of life for urban residents. This research provides important insights for policymakers and practitioners in their efforts to create sustainable and responsive urban communities.